2019
DOI: 10.1016/j.jclepro.2019.118014
|View full text |Cite
|
Sign up to set email alerts
|

Potential of circular economy implementation in the mechatronics industry: An exploratory research

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…CPD aims to maintain product value as long as viable, focusing on design methods that result in extending the useable life, either through easy maintenance or by ensuring reliability and durability (Chouinard et al, 2019; den Hollander et al, 2017). For this, the CPD approach presents three fundamental looping strategies: narrowing, slowing, and closing loops (Bocken et al, 2016).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…CPD aims to maintain product value as long as viable, focusing on design methods that result in extending the useable life, either through easy maintenance or by ensuring reliability and durability (Chouinard et al, 2019; den Hollander et al, 2017). For this, the CPD approach presents three fundamental looping strategies: narrowing, slowing, and closing loops (Bocken et al, 2016).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…If the case company does not investigate the market needs for remanufactured products, evidence that supports the development of remanufacturable products will be lacking. In their paper, Chouinard et al [40] stress the importance of researching customer needs in circular product design as well. Bressanelli et al [41] similarly found a lack of considering user needs for circular design in WEEE-industry research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies should assess how Industry 4.0 technologies effectively unlock the CE implementation, support the development of circular business models, and monitor product lifecycle [ 118 , 140 , 173 ]. Given that the progress of industrialisation can result in the exponential boom of several markets, including electronics, it is still unclear how product obsolescence [ 29 , 66 ] due to the acceleration rate of technological developments or the artificial limitation of product durability can hamper efforts to operationalise the CE and lead to unstainable production and consumption models.…”
Section: Findings Of Mpamentioning
confidence: 99%